2011 rapid excavation and tunneling conference proceedings - Redmond, Steve; Romero, Victor (Society for Mining, Metallurgy, and Exploration, Inc., 2011)
Every two years, industry experts and practitioners from around the world gather at the prestigious Rapid Excavation and Tunneling Conference (RETC) to learn about the latest developments in tunneling technology, and the signature projects that help society meet its growing infrastructure needs. Inside this authoritative 1608-page book, you'll find the 115 influential papers that were presented providing valuable insights from projects worldwide. You'll gain from the lessons learned-often the hard way-from large and demanding projects in difficult ground conditions. This book will take you u.